Conservative Management of a Radicular Cyst Associated with a Primary Molar: A Case Report - Rai, Alina; Poudel, Kabiraj; Dali, Mamta; Koirala, Bandana (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Radicular cysts associated with deciduous teeth are rare findings and affect mostly the mandibular teeth. Pain or loosening of tooth, swelling of jaw is a common clinical findings. A 7-year-old boy presented to the department with complaint of pain and swelling in the left side of face since one month. Orthopantomogram revealed radiolucent lesion with respect to the lower left second primary molar. Extraction of the offending tooth was done followed by marsupialization. Cystic lining sent for histopathological examination confirmed radicular cyst. Early diagnosis and treatment of radicular cyst is quite essential to avoid harm to the adjacent teeth and other vital structures, not to miss the essence of impact on the tender growing mind and body.